2018
DOI: 10.1080/07448481.2018.1462819
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal analysis of the relationships among daytime dysfunction, fatigue, and depression in college students

Abstract: Depression is related to a higher initial level of DD and its faster rate change which in turn, predicted end-semester fatigue, identifying one of the possible pathways through which depression impacts the functioning and health of affected students.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 46 publications
5
14
0
Order By: Relevance
“…Greater economic loss could lead to psychological distress, which may in turn increase the risk of fatigue. Similar findings were found in university students (Shim et al, 2019) before and during COVID-19 outbreak (Verma, 2020;Wang et al, 2020b). The relationship between fatigue and depression/anxiety were bidirectional (Thorsteinsson et al, 2019) (i.e., fatigue could increase the risk of depression and anxiety, and vice versa).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Greater economic loss could lead to psychological distress, which may in turn increase the risk of fatigue. Similar findings were found in university students (Shim et al, 2019) before and during COVID-19 outbreak (Verma, 2020;Wang et al, 2020b). The relationship between fatigue and depression/anxiety were bidirectional (Thorsteinsson et al, 2019) (i.e., fatigue could increase the risk of depression and anxiety, and vice versa).…”
Section: Discussionsupporting
confidence: 81%
“…In another study, around 85% of patients with head and neck cancer experienced fatigue (Bossi et al, 2019). In addition, college students, particularly those enrolled in healthrelated subjects, often suffered from fatigue (Dol, 2016;Pallant, Sullivan & Kaluzny, 2020;Shim et al, 2019). For example, one study found that the prevalence of fatigue was 16.5% among medical students (Tanaka et al, 2008), while the corresponding figure was even higher among nursing students (39.1%) (De Moraes Amaducci, De Correa Mota & De Mattos Pimenta, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, we observed no differences in component 7, daytime dysfunction, which refers to sleepiness while performing everyday activities. Previous studies looking at daytime dysfunction in university students [ 40 ] observed that it worsened as the academic year went on, although not significantly. Based on the results we obtained, it seems that this component and component 6 are those least affected by lockdown.…”
Section: Discussionmentioning
confidence: 91%
“…Tertiary-level students have high levels of distress, mental illness (such as depression), and suicidal ideation. [1][2][3][4][5][6][7] Systematic reviews in different countries have shown that these students have a high prevalence of depressive symptoms (11.0% to 34.0%), [8][9][10][11] which is higher than the World Health Organization estimated global prevalence of depression of 4.4%. 12 In Hong Kong, 68.5% of university students were reported to have mild-to-severe levels of depressive symptoms.…”
Section: Introductionmentioning
confidence: 99%